ПУТИ СНИЖЕНИЯ ТЕХНОГЕННОЙ НАГРУЗКИ НА ГОРНОДОБЫВАЮЩИЕ РЕГИОНЫ УКРАИНЫ - Хоменко, О.Е; Кононенко, М.Н; Миронова, И.Г; Юрченко, К.О (Національний гірничий університет, 2017)
Выполнен анализ деятельности горнодобывающих предприятий и установлены экологические риски для техногенно-нагруженных регионов Украины. Предложены пути снижения негативного влияния горных производств на окружающую среду, что позволят уменьшить техногенную нагрузку и предотвратить возможные экологические катастрофы.

Виконано аналіз діяльності гірничодобувних підприємств і встановлені екологічні ризики для техногенно-навантажених регіонів України. Запропоновано шляхи зниження негативного впливу гірничих виробництв на навколишнє середовище, що дозволять зменшити техногенне навантаження і запобігти можливі екологічні катастрофи.

Purpose. The analysis of environmental risks in the technogenically-loaded regions of Ukraine and development of possible ways of their decision. The methods. Complex method of a research including the analysis of indicators of the mining enterprises activity and their influence on the environment was used for purpose achievement. Findings. As a result of the analysis of activity of mining enterprises, environmental risks for the technogenically-loaded regions of Ukraine are established and ways of their decreasing are proposed. The originality Additional waste recycling, preservation of land surface, decreasing in pollution of the atmosphere are complex that allows to reduce environmental risks in the technogenically-loaded regions of Ukraine. Practical implications. Ways of decreasing of technogenic loading in mining regions by means of usage during mining of mineral deposits and technologies that reducing technogenic loading on regions are offered.
Keywords: mining enterprise; technogenic loading; ecological risk; waste recycling; surface preservation; atmosphere pollution